PERSEPSI TERHADAP PELAJARAN DAN PERFORMANSI GURU IPA FISIKA SISWA SMP NEGERI KOTA PEKANBARU - Zulirfan '; Zuhdi Maaruf; Adelia Alfama; Riza Andriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The aim of this study was to gain an overview of the perception of physics subject and performance of their physic teacher. The sample of this study was 342 students of one of Junior High School in Pekanbaru. Data were collected using a questionnaire perceptions of physics subject and physic teacher performance. Both instruments were qualified with valid and reliable test of the validity of the questionnaire using the product moment correlation and reliability using alpha Cronbach. Descriptive analysis of the data showed75.8% of students have a positive and highly positive perception towards science in daily life, 83.9% of the science and technology, 85.3% of the science influence on other subjects .Only a small percentage of students who gave a negative and very negative perception of the three indicators of perception. Meanwhile, 45.53% of students stated that the performance of their physics teachers are in the category of very high, 47.95% were in the high categoryand6.51% at the low and very low categories. These results indicate that the students of junior high school in Pekanbaru have a good perception of physics subject and physics teacher performance. Keywords: teachers’ performance, students’ perceptions, physicals cience